PERMASALAHAN MORAL MASYARAKAT ISLAM DARI PERSPEKTIF UNDANG-UNDANG - Abdullah, Raihanah (Jurnal Syariah, 2019)
The article discusses at length the ethical problems of Muslim society from Islamic perspective, as well as try to differentiate between moral, ethics and law and its relationship. It aLso makes a list of illegal doings in perspectives of criminal laws as well as, to Islamic law and then explains penalties for those offences committed by Muslims.